Kajian Numerik Perilaku Sambungan Kayu Geser Tunggal Menggunakan Elemen Balok dan Elemen Solid - Wijaya, Naga; Suryoatmono, Bambang; Tjahjanto, Helmy Hermawan (MEDIA KOMUNIKASI TEKNIK SIPIL, 2024)
Modelling single shear wood connection using solid elements is more accurate, especially in simulating the contact between the surface of the lag screw and the surface of the pre-drilled hole, but it is more complicated in terms of geometry and number of nodes. An alternative method is approached by modelling the lag screw as a beam element, with the limitations of modelling the contact interaction between the lag screw and timber members. In this study, diameter variations were also modelled to investigate joint behavior. To validate the model accuracy, a modelling was also performed in which the connectors and timber members were all modelled as solid elements and performed theoretical calculations. Numerical analysis was carried out by modelling the connection specimens using the finite element method in the ABAQUS software. The results showed that the connection capacity between solid element and beam element modelling are quite similar. The accuracy of modelling the lag screw as a beam element is lower at larger diameters and requires a method to correct the results.